Effect on the ratio of rice husks and palm oil mill effluent (POME) as to be fertilizer / Muhammad Saiful Sarudin ... [et al.] - Sarudin, Muhammad Saiful; Ismail, Puteri Nadhirah; Ahmad Samri, Syaza Damia; Sukor, Mohd Zaki
Palm Oil Mill Effluent (POME), a by-product of palm oil mills is usually produced in a large quantity. In Malaysia, palm oil currently occupies the largest acreage of farmed land. Palm oil sludge, commonly referred to, as palm oil mill effluent (POME) is brown slurry composed of 4-5% solids, mainly organic, 0.5-1 % residual oil, and about 95% water. The effluent also contains high concentrations of organic nitrogen. Palm oil mill effluent is a thick brownish liquid that contains high solids, oil and grease, COD and BOD values. Conversion of POME to organic fertilizer can be a sustainable energy for its disposal only when its effects on soil microbial and biochemical properties. Fertilizer is any material of natural or synthetic origin that is applied to soils or plant tissues to supply more or one plant nutrients that is essential to the growth of plants. Rice husks can be us1ed in compost and vermicomposting to obtain a high quality organic fertilizer in a short time. Rice husk contains a high content1 of silicon and potassium which have great potential for amending soil. The present investigation was aimed to study the effect on the ratio of rice husks and palm oil mill effluent as to be fertilizer. The use of rice husks as an organic fertilizer might play a vital role not only improving soil physical condition but also in improving plant nutrient